2024
DOI: 10.3390/life14020230
|View full text |Cite
|
Sign up to set email alerts
|

Laccases as Effective Tools in the Removal of Pharmaceutical Products from Aquatic Systems

Daniela Chmelová,
Miroslav Ondrejovič,
Stanislav Miertuš

Abstract: This review aims to provide a comprehensive overview of the application of bacterial and fungal laccases for the removal of pharmaceuticals from the environment. Laccases were evaluated for their efficacy in degrading pharmaceutical substances across various categories, including analgesics, antibiotics, antiepileptics, antirheumatic drugs, cytostatics, hormones, anxiolytics, and sympatholytics. The capability of laccases to degrade or biotransform these drugs was found to be dependent on their structural char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 106 publications
2
2
0
Order By: Relevance
“…In the case of OTC, biotransformation reached 36, 42, and 26% at 40, 30, and 20 • C and pH 6.0, respectively, whereas the enzyme alone reached a maximum of 11% at 20 • C, indicating that FNTL requires the addition of a redox mediator for the removal of OTC. These results are in agreement with previous studies indicating that significant antibiotic elimination by laccases usually requires the involvement of an appropriate mediator [40,82].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the case of OTC, biotransformation reached 36, 42, and 26% at 40, 30, and 20 • C and pH 6.0, respectively, whereas the enzyme alone reached a maximum of 11% at 20 • C, indicating that FNTL requires the addition of a redox mediator for the removal of OTC. These results are in agreement with previous studies indicating that significant antibiotic elimination by laccases usually requires the involvement of an appropriate mediator [40,82].…”
Section: Discussionsupporting
confidence: 93%
“…Subsequently, the hydroxyl at C6 was removed to form TC5, which could be further decomposed to produce TC6, TC7, and TC8 [ 89 ]. Similar reactions leading to the formation of degradation products with a smaller molecular size have been reported for biodegradation of TC by fungal laccases, [ 48 , 82 , 87 ].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Finally, it was found that this rate varied between 26.0% and 48.4% for antibiotics included in the tetracycline group, such as oxytetracycline, chlortetracycline, doxycycline, and tetracycline. These differences between the removal rates are thought to be due to the molecular structure of antibiotics [71,72]. However, the use of enzyme-based techniques also presents limitations.…”
Section: Degradation Techniques Of Antibioticsmentioning
confidence: 99%